Requirement for memory B-cell activation in protection from heterologous influenza virus reinfection - Leach, Sarah; Shinnakasu, Ryo; Adachi, Yu; Momota, Masatoshi; Makino-Okamura, Chieko; Yamamoto, Takuya; Ishii, Ken J; Fukuyama, Hidehiro; Takahashi, Yoshimasa; Kurosaki, Tomohiro (International immunology, 2019)
Memory B cells protect against heterologous influenza infection Abstract While two memory compartments, memory B cells and long-lived plasma cells, are thought to contribute to the successful establishment of memory recall responses, the unique roles of each cellular compartment are still unclear. Herein, by tracing influenza anti-hemagglutinin (HA)-specific antibodies in mice, we demonstrate that pre-existing antibodies secreted by long-lived plasma cells are essential for protection from reinfection with the same influenza virus, whereas protection from secondary infection with an antigenically distinct influenza virus requires memory B-cell activation. These activated memory B cells were largely specific for the conserved HA stem region, and generated sufficient levels of antibodies for protection from heterologous reinfection. Given that the anti-stem plasmablasts derived from the memory B cells were higher affinity than those from naive B cells, our results suggest that maturation of anti-stem memory B cells during primary influenza infection and their subsequent activation are required for protection from reinfection by mutant viruses.